MANAJEMEN PERPUSTAKAAN PERGURUAN TINGGI (STUDI DI PERPUSTAKAAN POLITEKNIK NEGERI BALI ) - Kenanga, Ni Putu Amanda Diah; Haryanti, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2024)
A company or institution requires management to organize and manage an institution, for example a library. Activities in the library require management to organize the activities in the library well. College Libraries are libraries that assist the university academic community activities at a university. College libraries are a repository for searching for information for the academic community. This study used qualitative method by conducting interviews with informants by conducting observations, interviews and notes. The results of this research are that the management system at the Bali State Polytechnic Library is regulated based on the Policy of the Director of the National Library of the Republic of Indonesia No. 13 of 2017 concerning National Standards for Higher Education Libraries.